Preoperative Three-Dimensional, Multiplanar Reconstruction Simulation, and Virtual Laminectomy Using VINCENT Software - Nozawa, Satoshi; Akiyama, Haruhiko; Iwai, Chizuo; Yamada, Kazunari; Fushimi, Kazunari (Journal of Spine Research, 2021)
Introduction: Although navigation in spinal surgery is effectively utilized, meticulous preoperative planning is still required for safe and successful surgery. We introduced a meticulous planning method using a three-dimensional (3D) image analysis system.Methods: Cases were analyzed using high-volume data, such as thin-slice CT images, using the software SYNAPS VINCENT (Fuji film). Multiplanar reconstruction (MPR), 3D image preparation, and virtual bone resection were conducted. Using the MPR images of patients with scoliosis, we measured the length and diameter of the pedicle screws (PS). The normally (Du) and carefully (Dm) measured diameters of 20 PS were compared statistically.Results: The average difference between Du and Dm was 0.69±0.09 (p < 0.01). The diameter of Dm was significantly increased compared to Du. Using VINCENT, we could accurately assess screw trajectory and bone condition before surgery. Additionally, we could effectively perform virtual laminectomy, foraminotomy, and PS insertion to correct a severely deformed spine.Conclusions: Based on careful planning using a 3D image analysis system, we could successfully perform a complex surgical procedure with little to no complications. This software is beneficial to spine surgeons and, with careful planning, has the potential to aid in reducing the intraoperative risk of vessel and nerve damage.